Zinc-titanium composite cluster as well as synthesis method and photoetching patterning application thereof
By regulating the type of ligand and introducing aromatic carboxylic acids with pushing electron groups, the problem of insufficient patterning resolution and etching resistance of zinc-titanium composite cluster photoresist in extreme ultraviolet lithography is solved, and high efficiency is achieved. Stable photoresist performance is improved, suitable for application scenarios with smaller feature sizes.
Patent Information
- Application Number
- CN202411417517.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-11
AI Technical Summary
Existing zinc-titanium composite cluster photoresist has insufficient pattern resolution and etch resistance in extreme ultraviolet lithography, especially in application scenarios with smaller feature sizes, and the impact on different ligand types is not fully understood. , resulting in incomplete understanding of the structure-effect relationship and exposure mechanism of photoresist.
By regulating the ligand type, the electron orbital distribution of the cluster is changed, and the photosensitiveness of zinc-titanium composite clusters is precisely controlled, thereby improving the sensitivity and resolution of the photoresist, and introducing aromatic carboxylic with pushing electron groups Acid optimizes the HOMO energy level and ligand dissociation energy of the cluster, and enhances etch resistance.
The photoresist is efficient, stable photosensitive and high resolution, which reduces exposure energy demand, improves production efficiency and cost-effectiveness, and avoids the resolution drop caused by acid diffusion, reaching the current industry's advanced level.
Smart Images

Figure CN119285683A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the fine chemical industry technology, and in particular to a zinc-titanium composite cluster and its synthesis and application. Background Art
[0002] With the rise of fields such as artificial intelligence, the demand for computer computing power in all walks of life is increasing day by day, which undoubtedly puts higher demands on the semiconductor industry. As a key link in the production of semiconductor chips, photolithography plays a decisive role in the performance of chips. In the exposure process, ultraviolet light will pass through a photomask with a specific pattern to irradiate the surface of the silicon wafer coated with a photoresist film layer. After irradiation, the photoresist will undergo a photochemical reaction. According to the different solubility changes before and after exposure, the photoresist can be divided into positive photoresist and negative photoresist. Positive photoresist refers to the part that is irradiated by ultraviolet light after exposure. The solubility increases during the development process, and vice versa, it is negative photoresist. Through this change in solubility, a specific pattern is transferred to the photoresist layer, and then the pattern is finally transferred to the surface of the silicon wafer through processes such as etching and stripping.
[0003] In order to meet the growing demand for computing power, the lithography process in the semiconductor industry is also constantly iterating. According to the Rayleigh formula CD = k1λ / NA, it can be seen that under the condition of a certain numerical aperture (NA) and process parameters (k1) of the lithography machine, the most effective way to reduce the critical dimension (CD) and improve the integration is to reduce the wavelength of the incident light during the exposure process. Therefore, the wavelength of the light source of the lithography machine has also undergone a transformation from 436nm-365nm-248nm-193nm-13.5nm. The current wavelength of 13.5nm extreme ultraviolet light (EUV) has been widely used in industrial production and has become the mainstream for the development of 3nm and below process technology.
[0004] Due to the sharp shortening of the wavelength of the light source, the energy carried by a single photon is also greatly increased to 92eV, which makes the photon density of EUV lower at the same dose. At the same time, since EVU light is easily absorbed, even if the current ASML lithography machine has been improved from the traditional lens optical path to the reflector optical path, the EUV efficiency that can finally reach the photoresist film layer is still not high. Therefore, in order to maximize the use of light sources and reduce production costs, in recent years, a series of metal elements with high EUV absorption have been introduced into EUV photoresists, such as metal nanoparticle photoresists, metal complex photoresists, metal oxide cluster photoresists, and metal-modified polymer photoresists have been developed.
[0005] Currently, there is only one literature published on zinc-titanium composite cluster photoresist, which is my previous article (https: / / doi.org / 10.1016 / j.cej.2024.152315). The design idea of this paper is to regulate the core of clusters with the same ligand (methacrylic acid); however, this type of photoresist still faces many challenges in practical applications in terms of lithography sensitivity, pattern roughness and resolution.
[0006] Existing ZnTi complex cluster photoresists require a relatively high EUV light dose (30 mJ / cm 2 ) can be achieved, which not only increases the manufacturing cost, but may also affect the stability of the photoresist and the quality of the pattern.
[0007] At present, only one zinc-titanium complex cluster photoresist with methacrylate as a ligand has been synthesized, and there is a lack of systematic research on the effects of different types of ligands on the performance of photoresists (such as sensitivity, pattern roughness and resolution). As a result, the structure-activity relationship of photoresists and their exposure mechanism are not yet fully understood, and further in-depth discussion is urgently needed.
[0008] Under existing technical conditions, the resolution and etching resistance of EUV photoresist during the patterning process still need to be improved, especially in application scenarios pursuing smaller feature sizes (such as 8nm and below). These defects have become a bottleneck restricting its development.
[0009] Because of the above-mentioned problems in the prior art, technical personnel in this field are in urgent need of improvement. Therefore, solving the above-mentioned problems is of great significance to promoting the development of EUV lithography technology. Summary of the invention
[0010] In order to overcome the defects of insufficient patterning resolution and poor etching resistance of EUV photoresists in the prior art, the present invention changes the electronic orbital distribution of the cluster by regulating the type of ligand, thereby achieving precise control of the photosensitivity of the zinc-titanium composite cluster, thereby achieving the purpose of improving the sensitivity and resolution of the photoresist and enhancing the etching resistance. The present invention aims to provide a more efficient and stable lithography solution to meet the semiconductor industry's demand for higher integrated chip manufacturing.
[0011] In order to achieve the above object, the technical solution of the present invention is: a type of zinc-titanium composite cluster, wherein the zinc-titanium composite cluster has the following structure of general formula I:
[0012]
[0013] In the general formula I,
[0014] R1 is selected from an alkyl group having 0-18 carbon atoms, an alkenyl group having 2-18 carbon atoms, an alkynyl group having 2-18 carbon atoms, a cycloalkyl group having 3-20 carbon atoms, a heterocycloalkyl group having 3-20 carbon atoms, a halogen, a nitro group, a cycloalkenyl group having 3-20 carbon atoms, or an aromatic group having 6-20 carbon atoms, wherein the aromatic group contains at least one or no substituent, and the substituent is a halogen, a nitro group, a sulfonic acid group, an alkyl group having 1-10 carbon atoms, an alkenyl group having 2-18 carbon atoms, an alkynyl group having 2-18 carbon atoms, or a fluoroalkyl group having 1-10 carbon atoms.
[0015] In a further preferred embodiment, R1 is selected from an alkyl group having 0-8 carbon atoms, an alkenyl group having 2-8 carbon atoms, an alkynyl group having 2-8 carbon atoms, a cycloalkyl group having 3-12 carbon atoms, a halogen, a nitro group or an aromatic group having 6-12 carbon atoms, wherein the aromatic group contains at least one or no substituent, and the substituent is a halogen, a nitro group, an alkyl group having 1-8 carbon atoms or an alkenyl group having 2-8 carbon atoms.
[0016] In a further preferred embodiment, R1 is selected from 0 / 1 carbon alkyl, vinyl, ethynyl, F atom, and nitro.
[0017] The present invention provides a method for synthesizing a zinc-titanium composite cluster having the above-mentioned general formula I structure:
[0018] The synthesis comprises: dissolving benzoic acid modified with an R1 substituent in an anhydrous organic solvent, adding the dissolved organic acid solution into a mixture of titanium isopropoxide and zinc acetate in a molar ratio of 1-5:1-5, and completely dissolving the organic acid solution, and allowing the obtained solution to stand at 25-60°C for 7-30 days under closed conditions, and washing, filtering and vacuum drying the obtained solid product after crystal precipitation to obtain a pure solid product.
[0019] The reaction formula is as follows:
[0020]
[0021] Furthermore, the molar ratio of benzoic acid modified with R1 substituent to titanium isopropoxide is 1-15:1, and the further preferred molar ratio range is 5-10:1.
[0022] Furthermore, the molar ratio of the benzoic acid modified with the R1 substituent to the organic solvent is 1 mmol: 1-20 mL, and the further preferred molar ratio range is 1 mmol: 2-14 mL.
[0023] Furthermore, the organic solvent is selected from one of the following mixed solutions: a mixed solution in which the molar ratio of isopropanol: dichloromethane is 1-5:1-5, a mixed solution in which the molar ratio of isopropanol: tetrahydrofuran is 1-8:1-5, a mixed solution in which the molar ratio of isopropanol: dichloromethane is 8-15:1-5, and a mixed solution in which the molar ratio of tetrahydrofuran: dichloromethane is 5-10:1-5; further preferably, the organic solvent is selected from one of the following mixed solutions: a mixed solution in which the molar ratio of isopropanol: dichloromethane is 1:1, a mixed solution in which the molar ratio of isopropanol: tetrahydrofuran is 2:1, a mixed solution in which the molar ratio of isopropanol: dichloromethane is 10:1, and a mixed solution in which the molar ratio of tetrahydrofuran: dichloromethane is 6:1.
[0024] The zinc-titanium composite cluster is expected to be applied in the following fields:
[0025] Semiconductor manufacturing industry: In extreme ultraviolet lithography technology, the photoresist of the present invention can be used to manufacture semiconductor chips with higher integration, promoting the development of next-generation high-performance computing devices.
[0026] Nanotechnology: Due to its high-resolution characteristics, this photoresist is also suitable for nanoscale precision manufacturing, such as nanosensors, nanoelectronic devices, etc.
[0027] Optical component manufacturing: In the microstructure processing of optical components, high-sensitivity and high-resolution photoresists can be used to manufacture complex optical components such as high-precision lenses, fiber optic connectors, etc.
[0028] In a further preferred embodiment, the zinc-titanium complex clusters are used in extreme ultraviolet lithography and electron beam lithography, and the zinc-titanium complex clusters are used as photosensitizers and resins in photoresist formulations.
[0029] Furthermore, the photoresist is prepared by the following method: adding chloroform to the zinc-titanium composite cluster, ultrasonically treating for 10 minutes and then filtering to obtain a photoresist solution.
[0030] Furthermore, the zinc-titanium composite cluster is used as a photosensitizer and resin in an electron beam photoresist formulation to complete patterning of lines with a line width of 8nm-25nm with high sensitivity in electron beam lithography.
[0031] Furthermore, the zinc-titanium composite cluster is used as a photosensitizer and resin in an EUV photoresist formulation, and can complete the patterning of 75nm-300nm periodic lines in EUV photolithography exposure, and a further preferred period is 75nm.
[0032] In summary, the present invention has the following beneficial effects:
[0033] 1. Since aromatic carboxylic acids have a higher boiling point, they have higher thermal stability than clusters with methacrylic acid as ligands in the published literature, which is more beneficial for the long-term storage of photoresists.
[0034] 2. The particle size of the zinc-titanium composite clusters described in the present invention is around 2nm, which is smaller and more uniform than the traditional CAR photoresist. At the same time, since no additives such as photoacid are required during the photolithography process, the post-bake (PEB) process can be omitted after exposure to reduce production costs. On the other hand, the resolution will not decrease due to acid diffusion during the exposure process. For example, Example 1 shows a line with a line width of about 9.6nm formed at a period of 70nm, and this resolution has reached the advanced level in the current industry.
[0035] 3. In the present invention, by introducing an aromatic carboxylic acid with an electron-pushing group into the cluster, the HOMO energy level of the cluster is increased. On the one hand, the vertical electron departure energy (VIP) of the cluster is reduced, so that the photoelectrons and secondary electrons generated during the exposure process increase and improve the exposure sensitivity. On the other hand, the dissociation energy of the ligand is reduced, which is also beneficial to the improvement of the sensitivity of the cluster. In particular, in Example 3, when 32wt% and 48wt% of hydroquinone (HQ) are added, the sensitivity of the photoresist reaches 36μC / cm 2 and 62μC / cm 2 , which is much higher than that of other examples without adding HQ, indicating that the sensitivity of the photoresist can be significantly improved by properly adjusting the ligand.
[0036] 4. The zinc-titanium composite cluster provided by the present invention is applied to extreme ultraviolet lithography and electron beam lithography. For example, the zinc-titanium composite cluster containing a carboxylic acid ligand preferably p-vinylbenzoic acid, during the exposure process, in addition to the electron-pushing effect on the vinyl group to increase the HOMO energy level of the cluster, the vinyl group will undergo free radical polymerization during exposure. The synergistic effect of the two greatly improves the sensitivity of the zinc-titanium composite cluster.
[0037] 5. In EUV lithography, Example 3 containing 32 wt% HQ has a thermal conductivity of only 25 mJ / cm 2 Exposure can be completed at an exposure dose of , which greatly reduces the required exposure energy compared to traditional materials, helping to improve production efficiency and reduce costs.
[0038] 6. By introducing different types of ligands (such as electron-pushing or electron-pulling groups), the electronic orbit of the photoresist can be effectively regulated, thereby controlling its photosensitivity and achieving fine-tuning of the lithography effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0040] Figure 1 is the crystal structure of the compound prepared in Example 1 of the present invention, indicating that the synthesized cluster is the expected structure;
[0041] Figure 2 This is the H NMR spectrum of the compound prepared in Example 1 of the present invention, which shows that the synthetic structure is accurate;
[0042] Figure 3 is the crystal structure of the compound prepared in Example 2 of the present invention, indicating that the synthesized cluster is the expected structure;
[0043] Figure 4 This is the H NMR spectrum of the compound prepared in Example 2 of the present invention, which shows that the synthetic structure is accurate;
[0044] Figure 5 is the crystal structure of the compound prepared in Example 3 of the present invention, indicating that the synthesized cluster is the expected structure;
[0045] Figure 6 This is the H NMR spectrum of the compound prepared in Example 3 of the present invention, which shows that the synthetic structure is accurate;
[0046] Figure 7 is the crystal structure of the compound prepared in Example 4 of the present invention, indicating that the synthesized cluster is the expected structure;
[0047] Figure 8 This is the H NMR spectrum of the compound prepared in Example 4 of the present invention, which shows that the synthetic structure is accurate;
[0048] Fig. 9 This is the NMR fluorine spectrum of the compound prepared in Example 4 of the present invention, which shows that the synthetic structure is accurate;
[0049] Fig.10 is the crystal structure of the compound prepared in Example 5 of the present invention, indicating that the synthesized cluster is the expected structure;
[0050] Fig.11 This is the H NMR spectrum of the compound prepared in Example 5 of the present invention, which shows that the synthetic structure is accurate;
[0051] Fig.12 is the crystal structure of the compound prepared in Example 6 of the present invention, indicating that the synthesized cluster is the expected structure;
[0052] Fig.13 The AFM images of the thin films prepared from the compounds prepared in Examples 1, 2, and 4 of the present invention under EBL illustrate that the zinc-titanium composite clusters can react under EBL to obtain patterns;
[0053] Fig.14 The AFM images of the thin films prepared from the mixture of Example 3 of the present invention and 32wt% / 48wt% hydroquinone under EBL illustrate that Example 3 containing different concentrations of free radical inhibitors can react under EBL to obtain patterns;
[0054] Fig.15 The contrast curve of the film prepared from the compounds prepared in Examples 1, 2, and 4 of the present invention under EBL shows that the exposure sensitivity of the zinc-titanium composite cluster decreases with the introduction of electron-withdrawing groups;
[0055] Fig.16 The contrast curve of the film prepared from the mixture of Example 3 of the present invention and 32wt% / 48wt% hydroquinone under EBL shows that the sensitivity of Example 3 decreases with the increase of the concentration of the free radical inhibitor;
[0056] Fig.17 The SEM images of periodic lines formed by thin films prepared from solutions of the compounds prepared in Examples 1, 2, 4, and 6 of the present invention under EBL illustrate that high-resolution images of zinc-titanium composite clusters can be obtained under EBL;
[0057] Fig.18 The SEM image of the periodic lines formed by the film prepared from the mixture of Example 3 of the present invention and 32wt% / 48wt% hydroquinone under EBL shows that the Example 3 containing different concentrations of free radical inhibitors can obtain high-resolution images under EBL;
[0058] Fig.19 The SEM and AFM images of periodic lines formed by the films prepared from the solutions prepared from Examples 1 and 3 of the present invention and 32 wt% hydroquinone under different EUVL doses illustrate that the zinc-titanium composite clusters can react under EUV and obtain high-resolution patterns, and that the electron-pushing olefin groups can greatly enhance the sensitivity of the zinc-titanium composite clusters under EUV. DETAILED DESCRIPTION
[0059] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0060] Example 1
[0061]
[0062] Dissolve 0.681g of p-toluic acid in a mixed solution of 2mL of isopropanol and 2mL of dichloromethane. Take another 20mL glass sample bottle, add 0.284g of titanium isopropoxide and 0.184g of zinc acetate, and finally add the organic solution of the above acid and seal the sample bottle. Use ultrasonic dissolution for 20min, and let it stand at room temperature for 7d after the solid is completely dissolved. Colorless crystals will form at the bottom of the sample bottle. After pouring out the mother liquor, wash it three times with anhydrous n-heptane and put the obtained solid into a vacuum drying oven. Vacuum dry it at 45℃ for 48 hours to obtain a dry solid product.
[0063] Crystal structure Figure 1 . Figure 1 is the crystal structure of the compound prepared in Example 1 of the present invention, indicating that the synthesized cluster is the expected structure;
[0064] Crystal data: Space Group: C2 / c, Cell: a=22.2623(6)b=22.2623(6)c=
[0065] 23.5196(7), alpha=90beta=93.0620(10)gamma=90.
[0066] 1 HNMR (400MHz, DMSO-d6, ppm): δ = 7.83 (d, J = 7.8Hz, 20H), 7.24 (d, J = 7.8Hz, 20H), 3.77 (s, 2H), 2.35 (s, 30H), 1.04 (d, J = 6.1Hz, 12H). For details, see Figure 2 .
[0067] Figure 2 The NMR hydrogen spectrum of the compound prepared in Example 1 of the present invention shows that the synthetic structure is accurate; Example 2
[0068]
[0069] Dissolve 0.613g of benzoic acid in 2mL of dichloromethane. Take another 20mL glass sample bottle, add 0.284g of titanium isopropoxide and 0.184g of zinc acetate, and finally add the organic solution of the above acid and seal the sample bottle. Use ultrasonic dissolution for 20 minutes, and after the solid is completely dissolved, let it stand at room temperature for 7 days. Colorless crystals will form at the bottom of the sample bottle. After pouring out the mother liquor, wash it three times with anhydrous n-heptane and put the obtained solid into a vacuum drying oven. Vacuum dry it at 45°C for 48 hours to obtain a dry solid product.
[0070] Crystal structure Figure 3 . Figure 3 is the crystal structure of the compound prepared in Example 2 of the present invention, indicating that the synthesized cluster is the expected structure;
[0071] Crystal data: Space Group: P-1, Cell: a=13.0090(7)b=13.6517(8)c=13.7854(7), alpha=92.897(2)beta=116.307(2)gamma=110.101(2).
[0072] 1 HNMR (400MHz, DMSO-d6, ppm): δ=7.96(d, J=7.5Hz, 20H), 7.51(t, J=7.3Hz, 10H), 7.43(t, J=7.5Hz, 20H), 3.83–3.73(m, 2H), 1.05(d, J=6.1Hz, 12H). For details, see Figure 4 . Figure 4 This is the H NMR spectrum of the compound prepared in Example 2 of the present invention, which shows that the synthetic structure is accurate.
[0073] Example 3
[0074]
[0075] Dissolve 0.741g of p-vinylbenzoic acid in a mixed solution of 2mL of dichloromethane and 1.5mL of tetrahydrofuran. Take another 20mL glass sample bottle, add 0.284g of titanium isopropoxide and 0.184g of zinc acetate, and finally add the organic solution of the above acid and seal the sample bottle. Use ultrasonic dissolution for 20 minutes, filter after the solid is completely dissolved, and let the filtrate stand at room temperature for 14 days. White flocculent crystals will form at the bottom of the sample bottle. After pouring out the mother liquor, wash it three times with anhydrous n-heptane and put the obtained solid into a vacuum drying oven. Vacuum dry it at 45°C for 48 hours to obtain a dry solid product.
[0076] Crystal structure Figure 5 .
[0077] Crystal data: Space Group: P-1, Cell: a=13.7176(10)b=14.0786(10)c=15.0858(10), alpha=109.467(2)beta=107.184(2)gamma=105.364(2).
[0078] Figure 5 This is the crystal structure of the compound prepared in Example 3 of the present invention.
[0079] 1 H NMR (400MHz, DMSO-d6, ppm): δ = 7.91 (d, J = 8.0Hz, 20H), 7.52 (d, J = 8.0Hz, 20H), 6.79 (dd, J = 17.7, 10 .9Hz, 10H), 5.93 (d, J = 17.6Hz, 10H), 5.36 (d, J = 10.9Hz, 10H), 3.77 (s, 2H), 1.04 (d, J = 6.1Hz, 12H). For details, see Figure 6 .
[0080] Figure 6 The NMR hydrogen spectrum of the compound prepared in Example 3 of the present invention shows that the synthetic structure is accurate; Example 4
[0081]
[0082] Dissolve 0.7g of p-fluorobenzoic acid in a mixed solution of 6mL of isopropanol and 0.6mL of dichloromethane. Take another 20mL glass sample bottle, add 0.284g of titanium isopropoxide and 0.184g of zinc acetate, and finally add the organic solution of the above acid and seal the sample bottle. Use ultrasonic dissolution for 20 minutes, filter after the solid is completely dissolved, place the filtrate in a high-temperature and high-pressure reactor, and let it stand in a constant temperature oven at 60℃ for 7d. Colorless crystals are generated at the bottom of the sample bottle. After pouring out the mother liquor, wash it three times with anhydrous n-heptane and put the obtained solid into a vacuum drying oven. Vacuum dry it at 45℃ for 48 hours to obtain a dry solid product.
[0083] Crystal structure Figure 7 . Figure 7 is the crystal structure of the compound prepared in Example 4 of the present invention, indicating that the synthesized cluster is the expected structure;
[0084] Crystal data: Space Group: P-1, Cell: a=13.2926(19)b=13.4912(19)c=14.562(2),alpha=86.204(6)beta=63.227(5)gamma=65.871(6).
[0085] 1 H NMR (400MHz, DMSO-d6, ppm): δ=8.23–7.84 (m, 20H), 7.24 (t, J=8.7Hz, 20H), 3.77 (p, J=6.2Hz, 2H), 1.04 (d, J=6.1Hz, 12H). Figure 8 .
[0086] Figure 8 This is the H NMR spectrum of the compound prepared in Example 4 of the present invention, which shows that the synthetic structure is accurate;
[0087] 19 F NMR (377MHz, DMSO-d6, ppm): δ = -104.03. Fig. 9 .
[0088] Fig. 9 The NMR fluorine spectrum of the compound prepared in Example 4 of the present invention shows that the synthetic structure is accurate; Example 5
[0089]
[0090] Dissolve 0.8g of p-ethynylbenzoic acid in a mixed solution of 4mL of dichloromethane and 4mL of isopropanol. Take another 20mL glass sample bottle, add 0.284g of titanium isopropoxide and 0.184g of zinc acetate, and finally add the organic solution of the above acid and seal the sample bottle. Use ultrasonic dissolution for 20min, filter after the solid is completely dissolved, let the filtrate stand for 30d, and light yellow crystals will form at the bottom of the sample bottle. After pouring out the mother liquor, wash it three times with anhydrous n-heptane and put the obtained solid into a vacuum drying oven, vacuum dry it at 45℃ for 48 hours to obtain a dry solid product.
[0091] Crystal structure Fig.10 . Fig.10 is the crystal structure of the compound prepared in Example 5 of the present invention, indicating that the synthesized cluster is the expected structure;
[0092] Crystal data: Space Group: C2 / c, Cell: a=17.0606(5)b=21.4103(9)c=25.6078(8), alpha=90beta=91.506(3)gamma=90.
[0093] 1H NMR (400MHz, DMSO-d6): δ=7.93(d, J=8.0Hz, 20H), 7.53(d, J=7.9Hz, 20H), 3.77(p, J=6.1Hz, 2H), 3.34(s, 10H), 1.04(d, J=6.1Hz, 12H). For details, see Fig.11 .
[0094] Fig.11 This is the H NMR spectrum of the compound prepared in Example 5 of the present invention, which shows that the synthetic structure is accurate;
[0095] Example 6
[0096]
[0097] Dissolve 1.67g of p-nitrobenzoic acid in a mixed solution of 12mL of tetrahydrofuran and 2mL of dichloromethane. Take another 20mL glass sample bottle, add 0.284g of titanium isopropoxide and 0.184g of zinc acetate, and finally add the organic solution of the above acid and seal the sample bottle. Use ultrasonic dissolution for 20 minutes, filter after the solid is completely dissolved, place the filtrate in a high-temperature and high-pressure reactor, and let it stand in a constant temperature oven at 60℃ for 7d. Crystals will form at the bottom of the sample bottle. After pouring out the mother liquor, wash it three times with anhydrous n-heptane. Put the obtained solid into a vacuum drying oven and vacuum dry it at 45℃ for 48 hours to obtain a dry solid product.
[0098] Crystal structure Fig.12 .
[0099] Crystal data: Space Group: P-1, Cell: a=14.8911(6)b==14.8911(6)c=15.9062(6), alpha=92.748(2)beta=117.641(2)gamma=112.536(2).
[0100] Fig.12 is the crystal structure of the compound prepared in Example 6 of the present invention, indicating that the synthesized cluster is the expected structure;
[0101] Example 7
[0102]
[0103] Dissolve 0.825g of p-dimethylaminobenzoic acid in a mixed solution of 8mL of dichloromethane and 4mL of isopropanol. Take another 20mL glass sample bottle, add 0.284g of titanium isopropoxide and 0.184g of zinc acetate, and finally add the organic solution of the above acid and seal the sample bottle. Use ultrasonic dissolution for 20min, filter after the solid is completely dissolved, let the filtrate stand for 15d, solid is generated at the bottom of the sample bottle, pour out the mother liquor and wash it three times with anhydrous n-heptane, put the obtained solid into a vacuum drying oven, and vacuum dry it at 45℃ for 48 hours to obtain a dry solid product.
[0104] Application Example 1
[0105] Application of a type of zinc-titanium complex cluster in electron beam lithography and extreme ultraviolet lithography:
[0106] To obtain a photoresist film layer with a thickness of about 30 nm, 8 mg of Examples 1 and 2, and 15 mg of Examples 4 and 6 were accurately weighed with a 1 / 10,000 balance and added into 1 mL of chloroform solution, ultrasonically oscillated for 10 min, and filtered twice with a 0.22 μm PTFE filter membrane to obtain a photoresist solution.
[0107] Due to the high sensitivity of Example 3, a free radical inhibitor is required to control the diffusion of free radicals during the photolithography process. 15 mg of Example 3 and 4.8 mg / 7.2 mg of hydroquinone (HQ) are accurately weighed using a 1 / 10,000 balance and added to 1 mL of chloroform solution. Ultrasonic oscillation is performed for 10 minutes, and the solution is filtered twice with a 0.22 μm PTFE filter membrane to obtain a photoresist solution.
[0108] During spin coating, 35 μL of photoresist solution was dropped on a 1 cm*1 cm silicon wafer using a pipette, the solution of Example 1 was rotated at 2000 rpm for 30 s, the solution of Example 2 was rotated at 6000 rpm for 30 s, and the remaining photoresist solutions were all rotated at 8000 rpm for 30 s, and then baked at 50° C. for 1 min to obtain a smooth film with a thickness of about 30 nm.
[0109] Test Example 1
[0110] The films prepared by the compounds provided in Examples 1, 2, 3, and 4 using the method described in the application example were subjected to normalized electron beam exposure tests, with an acceleration voltage of 2 kV, a square size of 5 μm*5 μm, a spacing of 5 μm, and a total of 8*8=64. After exposure, the film prepared in Example 3 was developed with 4-methyl-2-pentanone for 45 seconds, and the rest was developed with isopropanol for 30 seconds and then dried with nitrogen. The thickness variation diagrams of the above four zinc-titanium composite clusters were obtained using AFM, as shown in FIG. Fig.13 and Fig.14, the measured block thickness is normalized and then a contrast curve is plotted against the corresponding dose, see Fig.15 and Fig.16 . And use the following formula to calculate the contrast: The contrast ratios of the compounds prepared in the above examples are calculated and are shown in Table 1. The electron beam exposure sensitivity (D 100 ) are shown in Table 2. The HOMO energy levels of Examples 1, 2, 3, and 4 in Table 3 and the vertical electron departure energy (VIP) of each cluster and the dissociation energy of ligands at different sites in Table 4 were calculated by DFT.
[0111] Table 1 Contrast ratio of the above-mentioned example compounds
[0112]
[0113] Table 2 Sensitivity of the compounds in the above examples
[0114]
[0115] Table 3 HOMO and VIP of the above example compounds
[0116] Example HOMO(eV) VIP(eV) Example 1 -6.37 7.54 Example 2 -7.17 7.97 Example 3 -6.86 7.55 Example 4 -7.53 8.86
[0117] Table 4 Average ligand dissociation energy of the above-mentioned example compounds
[0118] Example Decarboxylation (eV) Deacylation (eV) Example 1 3.11 2.87 Example 2 3.76 3.42 Example 3 2.32 1.88 Example 4 5.27 4.74
[0119] Combination Fig.15 , Fig.16 As shown in Table 1, the contrast ratios of Examples 1, 2, 4 and Example 3+48 wt % HQ are between 1 and 2, which are suitable for current commercial photoresists and can easily obtain lines with more vertical sidewalls during periodic line patterning.
[0120] It can be seen from Table 2 that Example 3 has the highest sensitivity, followed by Example 1, followed by Example 2, and the lowest sensitivity is Example 4. Combined with the molecular structure, it can be seen that when electron-pushing groups are introduced on the aromatic acid ligands of the cluster, the exposure sensitivity of the cluster will be improved, while the introduction of electron-pulling groups will have the opposite effect. Combined with the molecular structure and Table 3, it can be seen that the introduction of electron-pushing groups will increase the HOMO energy level of the cluster, thereby increasing the VIP of the cluster, making it easier for the cluster to generate secondary electrons and photoelectrons to improve the reaction efficiency during exposure. Combined with the molecular structure and Table 4, it can be seen that the introduction of electron-pushing groups can also reduce the ligand dissociation energy of the cluster, which can also improve the sensitivity of the cluster during exposure.
[0121] The vinyl group introduced in Example 3 is not only an electron-pushing group, but also provides another way to improve the sensitivity of cluster lithography because it can undergo double bond cross-linking polymerization during exposure. Therefore, its sensitivity is greatly improved compared with other clusters, and is higher than the sensitivity of most publicly available photoresists, which is beneficial to improving the efficiency of photon utilization. In addition, high sensitivity means that less energy is required during exposure, which is beneficial to improving energy utilization efficiency and realizing industrialization.
[0122] Test Example 2
[0123] The zinc-titanium composite clusters provided in Examples 1, 2, 3, 4, and 6 were made into thin films using the method described in the application examples and subjected to electron beam exposure tests. The accelerating voltage of the electron beam exposure was 30 kV. After exposure, the film made in Example 3 was developed with 4-methyl-2-pentanone for 45 seconds, and the rest were developed with isopropanol for 30 seconds and then dried with nitrogen. The SEM results of the periodic patterns after development in Examples 1, 2, and 4 are shown in Figure 2. Fig.17 The SEM results of the periodic patterns of Example 3 containing different mass fractions of HQ after development are as follows: Fig.18 .
[0124] Combination Fig.17 and Fig.18 It can be seen that the compound shown in Example 1 forms lines with a line width of about 9.6nm at a period of 70nm; the compound shown in Example 2 forms lines with a line width of about 12.6nm at a period of 70nm; the compound shown in Example 4 forms lines with a line width of about 12.2nm at a period of 70nm; the compound shown in Example 6 forms lines with a line width of about 18.2nm at a period of 70nm; the compound shown in Example 3 containing 32wt% HQ forms lines with a line width of about 19.2nm at a period of 150nm; the compound shown in Example 3 containing 48wt% HQ (Ph-Sn-Oc) can also form lines with a line width of about 19.2nm at a period of 150nm.
[0125] Test Example 3
[0126] The films prepared by the method described in the application examples of Example 1 and Example 3 containing 32 wt% HQ were patterned at Shanghai Synchrotron Radiation Facility (SSRF) using X-ray Interference Lithography (XIL) under EUV (13.5 nm) exposure. After exposure, Example 1 was developed with isopropanol for 30 s, and Example 3 containing 32 wt% HQ was developed with 4-methyl-2-pentanone for 45 s, and both were dried with nitrogen after development.
[0127] The extreme ultraviolet exposure test uses grating diffraction exposure. The diffraction grating can form periodic lines with a period of 70nm (L / S). After exposure, the resulting pattern was measured using SEM and AFM. The test results are as follows: Fig.19 Example 1: When the exposure dose is 150 mJ / cm 2 Clear lines can be obtained, while Example 3 containing 32 wt % HQ has a high 2 It can be exposed at any time, indicating that the electron donation effect of the double bond and the cross-linking polymerization work together to greatly improve the sensitivity of this type of photoresist.
[0128] In summary, the zinc-titanium composite cluster photoresist provided by the present invention has the beneficial effects of high resolution and extremely high sensitivity.
[0129] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A zinc-titanium composite cluster, characterized in that: It has the following structure of general formula I: In the general formula I, R1 is selected from an alkyl group having 0-18 carbon atoms, an alkenyl group having 2-18 carbon atoms, an alkynyl group having 2-18 carbon atoms, a cycloalkyl group having 3-20 carbon atoms, a heterocycloalkyl group having 3-20 carbon atoms, a halogen, a nitro group, a cycloalkenyl group having 3-20 carbon atoms, or an aromatic group having 6-20 carbon atoms, wherein the aromatic group contains at least one or no substituent, and the substituent is a halogen, a nitro group, a sulfonic acid group, an alkyl group having 1-10 carbon atoms, an alkenyl group having 2-18 carbon atoms, an alkynyl group having 2-18 carbon atoms, or a fluoroalkyl group having 1-10 carbon atoms.
2. A zinc-titanium composite cluster according to claim 1, characterized in that: The R1 is selected from an alkyl group having 0-8 carbon atoms, an alkenyl group having 2-8 carbon atoms, an alkynyl group having 2-8 carbon atoms, a cycloalkyl group having 3-12 carbon atoms, a halogen, a nitro group, or an aromatic group having 6-12 carbon atoms, wherein the aromatic group contains at least one or no substituent, and the substituent is a halogen, a nitro group, an alkyl group having 1-8 carbon atoms, or an alkenyl group having 2-8 carbon atoms.
3. The zinc-titanium composite cluster according to claim 1, characterized in that: The R1 is selected from 0 / 1 carbon alkyl, vinyl, ethynyl, F atom, and nitro.
4. The method for synthesizing a zinc-titanium composite cluster according to claim 1, characterized in that: The reaction formula is as follows: The synthesis steps include: dissolving benzoic acid modified with an R1 substituent in an anhydrous organic solvent, adding the dissolved organic acid solution to a mixture of titanium isopropoxide and zinc acetate in a molar ratio of 1-5:1-5, and completely dissolving the organic acid solution; allowing the obtained solution to stand at 25-60°C for 7-30 days under closed conditions; washing, filtering, and vacuum drying the obtained solid product after crystal precipitation to obtain a pure solid product.
5. The method according to claim 4, characterized in that The molar ratio of benzoic acid modified with R1 substituent to titanium isopropoxide is 1-15:
1.
6. The method according to claim 4, characterized in that The ratio of the molar amount of benzoic acid modified with an R1 substituent to the organic solvent is 1mmol:1-20mL; the organic solvent is selected from one of the following: a mixed solution in which the molar ratio of isopropanol to dichloromethane is 1-5:1-5, a mixed solution in which the molar ratio of isopropanol to tetrahydrofuran is 1-8:1-5, a mixed solution in which the molar ratio of isopropanol to dichloromethane is 8-15:1-5, and a mixed solution in which the molar ratio of tetrahydrofuran to dichloromethane is 5-10:1-5.
7. Application of the zinc-titanium composite cluster as claimed in claim 1 in semiconductor manufacturing, nanotechnology, and optical component manufacturing.
8. The use according to claim 7, characterized in that: The application in the semiconductor manufacturing industry includes: application in extreme ultraviolet lithography and electron beam lithography, and the zinc-titanium composite cluster is used as a photosensitizer and resin in a photoresist formula.
9. The use according to claim 8, characterized in that: The photoresist is prepared by the following method: chloroform is added to the zinc-titanium composite cluster, and the solution is filtered after ultrasonic treatment for 10 minutes to obtain a photoresist solution; the zinc-titanium composite cluster is used as a photosensitizer and resin in an electron beam photoresist formula to complete the patterning of 8nm-25nm line width lines with high sensitivity in electron beam lithography.
10. The use according to claim 7, characterized in that: The zinc-titanium composite cluster is used as a photosensitizer and resin in an extreme ultraviolet photoresist formulation to complete the patterning of 75nm-300nm periodic lines in extreme ultraviolet lithography exposure.
Citation Information
Patent Citations
Preparation method of silver-modified porous carbon-based titanium dioxide photocatalyst for degrading phenol in water body
CN108654605A
Heterometallic titanium oxide cluster compound crystalline material and preparation method thereof, and application in dye photodegradation
CN111790451A
Metal oxygen cluster composition and photoetching patterning application
CN117008416A